The Development of Video Learning Materials on the Basic use of Scratch in Innovation Development and Design Courses to Promote Student Achievement at Thepsatri Rajabhat University - Autapao, Kanyarat (Journal of Roi Et Rajabhat University, 2024)
The purposes of this research were to 1) test the effectiveness of video learning materials on the Basic use of Scratch 2) compare the learning achievement of students before and after using the video learning materials on the Basic use of Scratch 3) test the learners’ satisfaction after using the video learning materials on Basic use of Scratch. The sample consisted of 35 students in Computer Education major who enrolled in the Innovation Development and Design Course in the first semester of the academic year 2022 by purposive sampling. The instruments for the study were 1) the effectiveness Assessment form and 2) Pretest and Posttest 3) the Satisfaction Assessment form. The data were analyzed by arithmetic mean, standard deviation, and The Wilcoxon Matches Pairs Signed Rank Test. The results of this research were 1) the effectiveness of video learning materials on Basic use of Scratch in the terms of media content, image, sound and presentation techniques were at the highest level in every aspect, the overall effectiveness was at the highest level 2) the learning achievement of students was higher at the .01 level of significance, and 3) the satisfaction towards learning management using the video learning materials on Basic use of Scratch in the terms of media content, learning media format and implementation were at the high level in every aspect, the overall satisfaction was at the high level.